How do aesthetics and tourist involvement influence cultural identity in heritage tourism? The mediating role of mental experience - Yang, Wei; Chen, Qiuxia; Huang, Xiaoting; Xie, Mei; Guo, Qiuqi (Frontiers in Psychology, 2022)
As heritage is precious treasure of human society, it is of vital importance to effectively develop heritage tourism resources and explore the mechanisms that influence tourists' cultural identity. This study has integrated the stimulus-organism-response framework with the cognition-affect-behavior model to construct a hypothetical model of heritage tourism aesthetics, tourist involvement, mental experience, and cultural identity. The questionnaires were collected at Qufu city, Shandong province in China to investigate the influence paths and mechanisms between heritage aesthetics, tourist involvement, mental experience, and cultural identity. The structural equation model was used to examine the relationship between the heritage tourism aesthetics-mental experience-cultural identity. The main findings: (1) the positive impact of aesthetics driving mental experience and cultural identity is significant; (2) the impact of tourist involvement on mental experience and cultural identity is significant; (3) the impact of aesthetics on cultural identity is not significant, and mental experience plays a fully mediating role between aesthetics and cultural identity in heritage tourism. This study provides a new research framework and perspective for the aesthetics, involvement, mental experience, and cultural identity of tourists in heritage tourism.